Phase Angle Control of Three Level Inverter Based D-STATCOM Using Neuro-Fuzzy Controller - Coteli, Resul; Deniz, Erkan; Dandil, Besir; Tuncer, Servet; Ata, Fikret (Univ Suceava, Fac Electrical Eng, 2012)
Distribution Static Compensator (D-STATCOM) is a shunt compensation device used to improve electric power quality in distribution systems. It is well-known that D-STATCOM is a nonlinear, semi-defined and time-varying system. Therefore, control of D-STATCOM by the conventional control techniques is very difficult task. In this paper, the control of D-STATCOM is carried out by the neuro-fuzzy controller (NFC) which has non-linear and robust structure. For this aim, an experimental setup based on three-level H-bridge inverter is constructed. Phase angle control method is used for control of D-STATCOM's output reactive power. Control algorithm for this experimental setup is prepared in MATLAB/Simulink and downloaded to DS1103 controller card. A Mamdani type NFC is designed for control of D-STATCOM's reactive current. Output of NFC is integrated to increase tracking performance of controller in steady state. The performance of D-STATCOM is experimentally evaluated by changing reference reactive current as on-line. The experimental results show that the proposed controller gives very satisfactory performance under different loading conditions.
Keywords: electric power quality; D-STATCOM; three-level H-bridge inverter; neuro-fuzzy controller; MATLAB